Flüchtlinge in Deutschland : Eine psychologische Analyse der Freiwilligen Rückkehr - Lersner, Ulrike von (My University, 2008)
In recent years, Voluntary Assisted Return Programmes (VARPs) have received
increasing funding as a potential way of reducing the number of refugees in EU member states. A number of factors may affect the mental well-being of returnees. These include adjustment to the home country following return, difficult living conditions, and long-term effects resulting from
the severe traumatic stress that had originally driven the affected out of their homes. Little is known about the extent to which these and other factors may promote or inhibit the willingness of refugees to return to their country of origin. The present pilot study investigated refugees who returned to their country of origin after having lived in exile in Germany for some 13 years.
The objectives of the present study were to examine the mental health status of refugees returning to their home country following an extended period of exile. We also aimed to assess the circumstances under which people decided to return, the current living conditions in their home country, and retrospective returnee evaluations of their decision to accept assisted return.
47 VARP participants were interviewed concerning their present living conditions, their views of their native country, and their attitudes towards a
potential return prior to actually returning as well as nine months after returning to their country of origin. I also interviewed a group of refugees (n = 50), which were also living in Germany but explicitly did not intend to return. In the study I included refugees and returnees, respectively, who returned to countries of the Former Yugoslavia, Turkey and Iraq. Mental health and well-being were assessed using the questionnaires PDS and EUROHIS and the structured interview M.I.N.I. Prior to returning to their home country, participants showed a prevalence rate of 53% for psychiatric disorders. After returning, this rate doubled to a sizeable 88%. Substantial correlations were found between the living situation in Germany, the disposition to return, and mental health. For two thirds of the participants, the decision to return was not voluntary. In the group of stayers we found a prevalence rate of 78% psychiatric disorders, a factor, which prevented return to the country of origin. In this group we also recorded substantial correlations between the living situation in Germany, disposition to return and mental health.
The results show that psychological strain among study participants was of a considerable magnitude. As a result of traumatic stress experienced during war and refuge, victims were vulnerable and not well equipped to cope with either post-migration stressors in exile or with a return to their country of origin. It is noteworthy that the majority returned under pressure from immigration authorities. Living conditions after return (such as housing, work, and health care) were poor and unstable. Participants also had great difficulty readapting to the cultural environment after having lived abroad for an average of 13 years. Current VARPs do not take these factors into account and are therefore not able to assist in a humanitarian reintegration of voluntary returnees.
Refugees in Germany: A psychological analysis of voluntary return
Keywords: refugee; mental health; voluntary return; reintegration; 150; Flüchtling; Rückkehr <Motiv>; Reintegration; Posttraumatisches Stresssyndrom; Psychische Gesundheit; Jugoslawien / Bürgerkrieg; Freiwilligkeit